Reliability and convergent validity of endurance indices derived from near-infrared spectroscopy and electromyography during a bilateral hanging task in amateur rock climbers - Kwong, Wai-Hang (2024)
Background: The ability to hang for a long time before forearm muscle fatigue is a crucial element of successful rock climbing. Electromyography (EMG) and near-infrared spectroscopy (NIRS) are also useful for measuring hemoglobin oxygenation for determining muscle endurance. In the present study, we aimed to evaluate the reliability and validity of muscle endurance indices derived using EMG and NIRS during a hanging task. Methods: A bilateral hanging task was designed to compare rock climbers and non-climbers in terms of the slopes of changes in the median frequency (MDF) and tissue oxygenation index (TOI) of forearm muscles. Results: A total of 17 participants were included in each of the two groups. The intraclass correlation coefficient (3,1) values derived for the MDF slope, TOI slope, ΔTOI, percentage change in oxygen concentration, and ΔHbt were 0.85, 0.73, 0.65, 0.75, and 0.65, respectively. The MDF slope, TOI slope, and ΔHbt differed significantly between the groups (p < 0.05). The MDF slope, TOI slopes, and ΔHbt were significantly correlated with V-scale levels for climbing (p < 0.05). Conclusions: The satisfactory reliability and observed distinctions between climbers and non-climbers imply that these indices are a valuable tool for assessing muscle endurance.